Strategi Smart Power dalam Menghadapi Ancaman Gerakan Organisasi Papua Merdeka Guna Mendukung Keamanan Nasional - Teguh Wiratama; Afrizal Hendra; Andries Andries (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
The security situation in Papua continues to be a sensitive issue affecting national stability, with the main threat coming from the Free Papua Organization (OPM). OPM seeks the separation of Papua from Indonesia through armed action, international campaigns, and propaganda, with a significant increase in violent incidents from 2015 to a peak in 2023. Although the Special Autonomy policy has been implemented, the measure has not been able to fully address the existing tensions. This study aims to analyze the Smart Power strategy in dealing with OPM threats and supporting national security, using qualitative descriptive methods and AHP SWOT analysis. The findings suggest that the success of this strategy is highly dependent on the integration of diplomacy, military power, political support, and infrastructure development. Operational collaboration between the TNI, the National Police, and BIN in implementing socio-economic programs plays a key role, with diplomacy supporting stability and conflict management. Understanding local culture is also a critical factor, where the integration of cultural approaches with infrastructure development efforts is aimed at easing tensions and increasing public support for the government. AHP's SWOT analysis identified key strengths such as inter-agency synergies, while weaknesses lie in reliance on consistent political support. The opportunity lies in improving well-being through sustainable development, while a major threat remains emerging from the OPM's activities and its international support. In conclusion, an adaptive Smart Power approach, with cross-sectoral collaboration and cultural sensitivity, is key in maintaining long-term stability and maintaining Indonesia's sovereignty in Papua.